2017
DOI: 10.1016/j.amepre.2017.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Time Physical Activity Among U.S. Adults With Arthritis, 2008−2015

Abstract: Percentage meeting each guideline was persistently low among adults with arthritis. The lower prevalence among adults with arthritis versus those without suggests that adults with arthritis need additional strategies to address potential barriers (e.g., pain, psychological distress, inadequate medical support) to physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 23 publications
4
29
1
Order By: Relevance
“…Murphy et.al., found that Asians were just as likely as Whites to report meeting aerobic PA guidelines but did not address muscle strengthening physical activity guidelines. (14) In our study, Latinos were as likely as Whites to meet guidelines for both types of physical activity, which is consistent with a prior study. (14) African Americans were more likely than Whites to meet muscle strengthening guidelines; this may be due to cultural preferences for weight lifting/strengthening exercises or avoiding over-exertion.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Murphy et.al., found that Asians were just as likely as Whites to report meeting aerobic PA guidelines but did not address muscle strengthening physical activity guidelines. (14) In our study, Latinos were as likely as Whites to meet guidelines for both types of physical activity, which is consistent with a prior study. (14) African Americans were more likely than Whites to meet muscle strengthening guidelines; this may be due to cultural preferences for weight lifting/strengthening exercises or avoiding over-exertion.…”
Section: Discussionsupporting
confidence: 92%
“…The proportions of those with arthritis who meet aerobic and strengthening guidelines in our study are similar to those found in a previous study of the U.S. populationapproximately 36% and 18%, respectively. (14) In our study, a greater proportion of African Americans and Latinos, compared to Whites, received a physician recommendation to exercise. They were also more likely to report severe joint pain and activity limitations than Whites in absolute terms.…”
Section: Discussionmentioning
confidence: 67%
“…For adults with arthritis, low impact physical activity, such as walking, is a recommended approach for symptom management, but few get sufficient physical activity . Prior studies among people with arthritis have shown walking improves symptoms (pain, stiffness, and fatigue), function (self‐reported and physical performance measures), mood, and quality of life .…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that physical activity is specifically associated with a reduced risk of subsequent function decline and disability in persons with or at higher risk for knee OA. However, the proportion of these individuals engaging in the recommended levels of physical activity is very low . This low level of physical activity relates in part to concerns that physical activity will damage the knee joint .
Among persons at higher risk of knee osteoarthritis, the proportion engaging in recommended levels of physical activity is low, in part due to concerns that such activity will damage the knee.
…”
Section: Introductionmentioning
confidence: 99%